Creating a Cooperative Classroom Through Implementation of STAD Method for Biology Learning - Yaduvanshi, Sangeeta; Singh, Sunita (SCHOOL SCIENCE, 2021)
In the past decade, teaching was considered as interaction between teacher and students and focused on the transfer of knowledge from the brain of teacher to the brain of students. But in the present century, knowledge sources are vast and role of the teacher is shifted from knowledge giver to facilitator for knowledge creation. So, to address the need of present society, teacher educator should quest for some innovative pedagogical practices, which can equip our young learner with skills like problem solving and critical thinking and values, such as harmony and cooperation. These skills and values can enable our learner to face the challenges of this fast growing society. Therefore, in the present paper the authors attempt this to create cooperative learning environment within the Biology classroom through implementing the lay out plan based on Student Test Achievement Division (STAD) method of cooperative learning. Incorporation of this method may prove helpful for teacher and learner to achieve their learning goals in the light of contemporary demand of society.